PENGARUH SUNSET POLICY, TAX AMNESTY DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris di Kpp Pratama Batu) - Isa Ansori; jeni Susyanti (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This is the purpose of Sunset Policy analysis, Tax Amnesty, Tax Pinalties on Tax Compliance at KPP Pratama Batu. The population of this research is all taxpayers registered at KPP Pratama Batu, the number of samples in the survey are 100 people who are taxing at KPP Pratama Batu. Sampling is done using purposive sampling method. Method of data analysis used test validity, experiment, classification test classification, linear regression analysis, partial test (t), simultaneous test (f), determination coefficient (R²).Based on the result of data analysis, it is known that sunset policy has a negative and insignificant effect on taxpayer compliance. The result of t test equal to -0.254 with significant value equal to (0,800)> 0,05. Tax amnesty has a positive and significant effect on tax compliance. The result of t test count 4,144 with significant value equal to (0.000) <0.05. Tax Pinalties has a positive and significant effect on taxpayer compliance. The result of t test is 3,135 with significant value equal to (0.002) <0.05. Tax Compliance Variable can be explained by Sunset Policy, Tax Amnesty and Tax Pinalties variable of 20,7 % and the remaining 79,3% is influence by other things not examined in this research.Keywords: Sunset Policy, Tax Amnesty, Tax Pinalties, Tax Compliance.